ANALYSING THE MAIN INDICATORS OF GLOBAL TOURISM FLOWS IN EVOLUTION AND STRUCTURE - Smaranda SIMONI; Daniela MIHAI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Tourism is one of the most important economic sectors and the largest industry in the world, as it contributes to 5% of gross domestic product (GDP) worldwide and 6-7% of total employment. The international tourist flow has increased significantly during the latest 15 years. In 2011 there was a record number of international tourist arrivals (980 million), although during this year the global economic recovery has been slow and there have been major political changes in the Middle East or North Africa and natural disasters in Japan. The UNWTO forecasts show that the record of 1 billion international tourists (growth rate of 3-4%) will be reached in 2012.